(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hien PTT, Hang VTT, Cham LTT. 2024. Genetic diversity of Rose apple (Syzygium samarangense) varieties based on ISSR molecular markers. Biodiversitas 25: xxxx. Rose apple (Syzygium samarangense) exhibits a rich diversity in its varieties, metabolic compounds, and biological activities. Genetic diversity studies are crucial in understanding plant species taxonomy and evolutionary history. They provide a roadmap for researchers to trace the relationships between different varieties and offer insights into the evolutionary processes that have shaped the diversity within the species. Many traditional or indigenous varieties of plants may harbor unique traits adapted to specific local conditions. This study, therefore, holds immense value as it aims to evaluate the genetic relationship among rose apple varieties in Vietnam using morphological characteristics and ISSR markers. Sixteen local varieties of rose apple were collected from provinces in Vietnam for this purpose. The morphological characteristics of leaves and fruits were compared among samples, and the genetic diversity was evaluated using ISSR markers. The results revealed significant morphological diversity in the leaf base, blade shape, leaf color, and fruit shape and size. Based on the DNA profiles of 15 ISSR markers, 102 amplicons were produced, and the percentage of polymorphism ranged from 57 to 100%. The dendrogram constructed using the UPGMA method classified these varieties into two main clusters with a genetic diversity of 64%. Such comprehensive information underscores the genetic diversity among S. samarangense, thereby contributing to the germplasm resources for future plant breeding programs.